Clinical effects and safety of semi-solid feeds in tube-fed patients: a meta-analysis and systematic review - Feng, Limei; Xiang, Dingchao; Wu, Youping (Frontiers in Nutrition, 2024)
Background: Enteral nutrition is a very important treatment for critical ill patients. This metaanalysis aimed to evaluate the clinical effects and safety of semi-solid feeds in tube feeding patients.: Two researchers searched PubMed, Clinical trials, Embase, Cochrane Central Register of Controlled Trials, Web of Science and Cochrane library, China National Knowledge Infrastructure (CNKI), Wanfang, Weipu databases for randomized controlled trials (RCTs) on the clinical effects and safety of semi-solid feeds in tube feeding patients until October 10, 2023. Quality evaluation tool recommended by Cochrane library was used to evaluate the quality of included RCTs. The RevMan 5.4 software was used for data analysis.Results: A total of 8 RCTs involving 823 tube feeding patients were included in this meta-analysis.Synthesized outcome indicated that semi-solid feeds reduced the incidence of diarrhea (RR=0.32, 95%CI:0.20 0.50, P<0.001), vomiting (RR=0.31, 95%CI:0.15 0.64, P=0.002), abdominal distension (RR=0.41, 95%CI:0.22 0.76, P=0.005), length of ICU stay (MD=-3.61, 95%CI: -6.74 -0.48, P=0.02) and length of hospital stay (MD=-7.14, 95%CI: -10.31 -3.97, P<0.01) in tube feeding patients. No effect on the 30-day mortality (RR=0.55, 95%CI: 0.19 1.56, P=0.26) were found. No publication bias was detected by the Egger test results (all P>0.05).Conclusions: Semi-solid feeds are beneficial to reduce the incidence of diarrhea, abdominal distension, vomiting and hospital stay. More high-quality studies are needed to verify the effects of semi-solid feeds on mortality in the future.